1994
DOI: 10.1159/000176412
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role for Autoantibodies in Left Ventricular Hypertrophy

Abstract: The purpose of the study was to investigate the possible role of autoantibodies in the development and type of left-ventricular hypertrophy (LVH). Three groups of subjects were studied:15 patients with hypertrophic cardiomyopathy (HCM; 11 males, 4 females; mean age 50.0 ± 16..3 years); (b) 15 patients with essential hypertension (10 males, 5 females; mean age 56.8 ± 13.5 years) with normal renal function and serum electrolytes and (c) 15 male athletes (mean age 20.8 ± 5.9 years). The control group consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Inflammation is involved in cardiac remodeling and activation of complement cascade accompanies cardiovascular disturbances both in humans and rodents ( 96 , 97 ). C3 level has been shown to be elevated in serum of patients with left ventricular hypertrophy ( 98 ), in hypertensive patients ( 99 ) and more recently was recognized as a marker of hypertrophic cardiomyopathy ( 100 ). However we could not point at the immune proteins as biomarkers for monitoring the cardiac recovery because we observed upregulation of complement cascade proteins in cardiac muscle but not in the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is involved in cardiac remodeling and activation of complement cascade accompanies cardiovascular disturbances both in humans and rodents ( 96 , 97 ). C3 level has been shown to be elevated in serum of patients with left ventricular hypertrophy ( 98 ), in hypertensive patients ( 99 ) and more recently was recognized as a marker of hypertrophic cardiomyopathy ( 100 ). However we could not point at the immune proteins as biomarkers for monitoring the cardiac recovery because we observed upregulation of complement cascade proteins in cardiac muscle but not in the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyopathies might also be organ‐specific autoimmune disorders, perhaps in genetically predisposed individuals (Popovici et al , 1996; Badorff et al , 1997). In both HCM and DCM patients, autoimmune phenomena have been described (Boudonas et al , 1994; Badorff et al , 1997). Differences or similarities between these diseases and the other organ‐specific autoimmune diseases have not so far been described.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune mechanisms are likely to be involved in the process of disease development (Caforio et al 1996; Rose & Hill, 1996; Penninger et al , 1997; Matsumori, 1996; Schwimmbeck et al , 1996; Badorff et al , 1997). We have previously described cellular and humoral autoimmune reactivity against arterial and myocardial antigens in patients with hypertrophic cardiomyopathy (HCM) (Boudonas et al , 1994; Lefkos et al , 1995). The purpose of the present study is to investigate which pattern of immune response (Th 1 or Th 2 ) type is involved in the autoimmune process and/or what differences, if any, exist between HCM and dilated cardiomyopathy (DCM), by analysing the basic cytokines secreted from phytohaemagglutinin (PHA)‐cultured T cells, in the presence of relevant myocardial antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Some small HCM cohort studies have been performed in the past, revealing, among other effects, an increase in the number of patients with elevated AAbs against G-proteincoupled β1 and Muscarin-2 receptors (β1-AAb and M2-AAb) [151][152][153]. A recent study with 134 HCM patients (and 40 controls) confirmed these past results and also showed that the concentration of M2-AAb in HCM patients with a family history of SCD or atrial fibrillation was significantly higher [154].…”
Section: Autoantibody Biomarkers In Hcm Dcm and Acmmentioning
confidence: 99%